Paraneoplastic Raynaud's phenomenon manifesting before the diagnosis of lung cancer. (3rd July 2012) - Madabhavi, Irappa; Revannasiddaiah, Swaroop; Rastogi, Madhup; Gupta, Manoj Kumar
Abstract : This description pertains to a previously healthy gentleman aged 54 years who developed symptoms coherent with Raynaud's phenomenon. The patient never had any prior episodes of peripheral cyanosis. The patient's first presentation was in summer and the paroxysms of peripheral cyanosis were not associated with any specific aggravating factor. The paroxysms went on to become more severe and painful across a span of 6 months, when he also developed non-radiating pain in the right lateral chest-wall, which would aggravate after episodes of cough. A chest roentgenogram then demonstrated the presence of a mass lesion in the right lung and a fine-needle-aspiration cytology confirmed malignancy- an adenocarcinoma. There was a dramatic relief in pain and a reduction in the intensity and duration of paroxysms of peripheral cyanosis within 2-weeks of initiation of chemotherapy for lung cancer.